2018
DOI: 10.24823/sibbaldia.2018.255
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Genetic Structure of Two Closely Related Dipterocarp Species, Dryobalanops aromatica C.F. Gaertn. and D. beccarii Dyer

Abstract: Large-scale genetic structure revealed in tree populations in SE Asia, as well as in many temperate forests, has been shaped by climatic fluctuation in the late Pleistocene, most importantly by that in the last glacial period. In a comparative study of the phylogeographic patterns of two closely related dipterocarp species, Dryobalanops aromatica C.F.Gaertn. and D. beccarii Dyer, we investigated how changes in land area associated with changes in climate affected large-scale genetic structure. We examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
2
4
0
1
Order By: Relevance
“…Previous studies mainly focused on morphological and ecological characteristics ( Nghia 2005 ; Bien and Huong 2011 ). In our study, D. condorensis maintained relatively low genetic diversity ( N A = 2.4, H O = 0.296 and H E = 0.324) compared with previously published studies for some other species, such as S. leprosula ( Ng et al 2004 ), S. robusta ( Pandey and Geburek 2009 ), D. aromatica ( Harada et al 2018 ), and D. dyeri ( Tam et al 2020 ). However, our results showed a similar level of genetic diversity found previously in several studies, P. malaanonan ( Abasolo et al 2009 ), Shorea javanica ( Rachmat et al 2012 ), D. alatus ( Tam et al 2014 ) and H. odorata ( Trang et al 2014 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies mainly focused on morphological and ecological characteristics ( Nghia 2005 ; Bien and Huong 2011 ). In our study, D. condorensis maintained relatively low genetic diversity ( N A = 2.4, H O = 0.296 and H E = 0.324) compared with previously published studies for some other species, such as S. leprosula ( Ng et al 2004 ), S. robusta ( Pandey and Geburek 2009 ), D. aromatica ( Harada et al 2018 ), and D. dyeri ( Tam et al 2020 ). However, our results showed a similar level of genetic diversity found previously in several studies, P. malaanonan ( Abasolo et al 2009 ), Shorea javanica ( Rachmat et al 2012 ), D. alatus ( Tam et al 2014 ) and H. odorata ( Trang et al 2014 ).…”
Section: Discussionsupporting
confidence: 66%
“…To date, genetic research on D. condorensis has been limited. However, previous studies have shown high genetic variability in some dipterocarp species, such as Shorea leprosula ( Ng et al 2004 ), S. robusta ( Pandey and Geburek 2009 ), Dryobalanops aromatica ( Harada et al 2018 ) and Dipterocarpus dyeri ( Tam et al 2020 ), reflecting the life history traits and mating system. Several threatened dipterocarps have low genetic variability, such as Parashorea malaanonan ( Abasolo et al 2009 ), Dipterocarpus alatus ( Tam et al 2014 ) and Hopea odorata ( Trang et al 2014 ) suggesting the loss and fragmentation of habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Kỹ thuật Microsatellite (SSR -simple sequence repeats) là một trong những công cụ được sử dụng phổ biến cho việc đánh giá đa dạng di truyền ở thực vật và kỹ thuật này có tiềm năng, liên quan đến đa hình cao và tính kế thừa đồng trội trong genome, và lợi thế cho việc nghiên cứu di truyền các loại cây quý hiếm. Trên thế giới, kỹ thuật Microsatellite được ứng dụng phổ biến cho các nghiên cứu về đa dạng di truyền đối với một số loài cây họ Dầu (Rachmat et al, 2012;Trang et al, 2014;Harada et al, 2018;Vu et al, 2019).…”
Section: Tóm Tắtunclassified
“…Due to their distribution across all genomes, their polymorphism, and their reproducibility [17], microsatellite markers, i.e., simple sequence repeats (SSRs), have been widely used to investigate genetic diversity, population structure, gene flow, and mating systems in plants [18,19]. For the purpose of species conservation and management [20][21][22][23][24], nuclear microsatellites have been used in studies of genetic diversity focusing on certain dipterocarp species, such as Dryobalanops lanceolata in Sarawak, Malaysia [25], Shorea curtisii in Sarangor, Malaysia [26], and Dipterocarpus tempehes in Sarawak, Malaysia [27]. The exploration of genetic variability within and among populations of D. turbinatus is of crucial importance for species conservation, management, and restoration.…”
Section: Introductionmentioning
confidence: 99%